Ibn Al-Zaghuni’s approach to his jurisprudential choices - prostration of forgetfulness and voluntary prayer chapter as a sample - Hasan, Abeer Farhan; Al-Shahrani, Hussain Mualwi (Journal of Islamic Sciences, 2023)
This study aims to identify Ibn Al-Zaghuni through his biography and demonstrate his approach in his jurisprudential choices through the chapter on the prostration of forgetfulness and prayer volunteering. This study depends on both inductive and deductive approaches, and it has results, one of them is that Ibn Al-Zaghuni was a scholar with his choices that were transmitted by the scholars of the Hanbali doctrine. The characteristics of his choices: contradicting the well-known choices of the doctrine in the two cases of the study, the scholars disagreed with him and weakened his choice in one case, some of the scholars agreed with him in the second case, and his evidence was mostly based on intellectual reasoning.
Keywords: Approach; Ibn Al-Zaghuni; jurisprudential choices; prostration of forgetfulness; prayer volunteering